Cytotoxicity of Tetrahydropentagamavunon-0 (THPGV)-0 and Tetrahydropentagamavunon-1 (THPGV-1) in Several Cancer Cell Lines - Ikawati, Muthi; Purwanto, Heri; Imaniyyati, Niar Nurul; Afifah, Anis; Sagiyo, Marrita Langgeng; Yohanes, Jasson; Sismindari, Sismindari; Ritmaleni, Ritmaleni (Indonesian Journal of Pharmacy, 2018)
Tetrahydropentagamavunon-0 (THPGV-0) and Tetrahydro-pentagamavunon-1 (THPGV-1), are analogs of a curcumin metabolite, tetrahydrocurcumin, and a derivate of Pentagama-vunon-0 (PGV-0) and Pentagamavunon-1 (PGV-1), respectively.  THPGV-0 and THPGV-1 have been successfully synthesized and are investigated for their anticancer potency.  Cytotoxic assays were performed toward several cancer cell lines to determine values of the IC50 against those cell lines. Assessing cytotoxicity in Vero normal cell line showed the selectivity of those compound.  THPGV-1 showed highest cytotoxic activity in lymphoma Raji cells, a suspension cell line, with an IC50 of 180mM.  Both THPGV-0 and THPGV-1 showed similar potencies in T47D breast cancer cell line with IC50 values of 250-270mM.  Regardless their high selectivity, however, cytotoxic activities of THPGV-0 and THPGV-1 were lower compared to PGV-0 and PGV-1 in HeLa cervical, T47D breast, and WiDr colon cancer cell lines.  Further study using different types of cancer cell lines and confirmation of cell viability by another assays and apoptosis detection may give more benefit.